Chimeric cytochrome P450 3A4 used for in vitro prediction of food–drug interactions. (6th August 2020) - Sadeghi, Sheila J.; Di Nardo, Giovanna; Gilardi, Gianfranco
Abstract: Inhibition of cytochrome P450 (CYP)‐mediated drug metabolism by dietary substances is the main cause of drug–food interactions in humans. The present study reports on the in vitro inhibition assays of human CYP3A4 genetically linked to the reductase domain of bacterial BM3 of Bacillus megaterium (BMR) resulting in the chimeric protein CYP3A4–BMR. The activity of this chimeric enzyme was initially measured colorimetrically with erythromycin as the substrate where K M values similar to published data were determined. Subsequently, the inhibition assays with three different dietary products, grapefruit juice, curcumin, and resveratrol, were carried out with the chimeric enzyme both in solution and immobilized on electrode surfaces. For the solution studies, nicotinamide adenine dinucleotide phosphate was added as the electron donor, whereas the need for this cofactor was obviated in the immobilized enzyme as it was supplied by the electrode. Inhibition of the N‐demethylation of erythromycin by CYP3A4–BMR chimera was measured at increasing concentrations of the different dietary compounds with calculated IC50 values of 0.5%, 31 μM, and 250 μM for grapefruit juice, curcumin, and resveratrol measured in solution compared with 0.7%, 24 μM, and 208 μM measured electrochemically, respectively. These data demonstrate the feasibility of the use of both CYP3A4–BMR chimera as well as bioelectrochemistry for in vitro studies of not only drug–food interactions but also prediction of adverse drug reactions in this important P450 enzyme. Abstract : Inhibition of chimeric CYP3A4‐BMR by grapefruit juice, curcumin and resveratrol measured in solution and immobilised on carbon electrodes.